Drivers of attitudes toward luxury and counterfeit products: the moderating role of interpersonal influence. Issue 2 (30th March 2022) - Iyer, Rajesh; Babin, Barry J.; Eastman, Jacqueline K.; Griffin, Mitch
Abstract : Purpose: This study explores consumers' motivations to purchase luxury and counterfeit products using an international sample. In addition, it also examines the moderating role of interpersonal influence on this process. This study seeks to examine if the consumers who demand the highest quality express a preference for luxury goods over counterfeit goods. Design/methodology/approach: Survey research was employed to subjects from the USA, India, China and Russia. Responses from US and India consumers were collected using online software, whereas responses from China and Russia were collected with the help of a local market research firm. Findings: The findings of the study indicate that consumers tend to show similar reactions based on the luxury and counterfeit consumption process examined here. In terms of interpersonal influence as a moderator, however, the study found it significantly impacts status seekers' attitude toward luxury and how a perfectionist shopper perceives counterfeit consumption. Originality/value: This study is one of the first in the literature to empirically address both luxury and counterfeit consumption. Further it considers consumers from multiple countries with high levels of luxury good purchases.